Three-, four-, and five-day microcycles: the normality in professional football - Gualtieri, A.; Vicens-Bordas, J.; Rampinini, E.; Ferrari Bravo, D.; Beato, M. (International Journal of Sports Physiology and Performance, 2024)
Purpose This study aimed to quantify training and match-day (MD) load during 3-, 4-, and 5-day microcycles in professional adult football, as well as to analyze the effect of the microcycle length on training load produced the day after the match (MD + 1) and the day before the match (MD - 1).